(3Yjhf GdCOdI aj eSGFd GdNdGa Hjf abgGA GdCeUGQs - (3CHh GdMSf Ydj Hf YeQ Hf CMeO GdeGdcj GdHZOGOjs ((3eMeO Hf YHO GdbGgQ Hf eMeO s)
(3ChdgG (B:s
(3SCdJehfi CQTOce Gddg Cf CLeY dce eG hbY Edqj ef eSGFd GdNdGa Hjf eGdc Hf CfS QMeg Gddg hHjf WGFaI ef abgGA GdCeUGQ QMeg Gddg Ydjge hCf CHjf eG YdeJg ef GdMLL ai Pdc , hCf CPcQ LedI ef Pdc s
(3BNQgG (B:s
(3eSFdI bGd eGdc (B: (3` QMeg Gddg ` hef aGJg TF ef UdGI GdEeGe aEfg jbVi eG aGJg (B( (3ef cJGH GdUdGI (B) s
(3fSNI fajSI LOkGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(1088) s
Keywords: (3GNJdGa GdabgGAs